Crop ontology: vocabulary for crop-related concepts - Matteis L; Chibon P; Espinosa, H.; Skofic, M.; Finkers R; Bruskiewich, R.; Hyman, Glenn G.; Arnaud, Elizabeth (2013)
A recurrent issue for data integration is the lack of a common and structured vocabulary used by different parties to describe their data sets. The Crop Ontology (www.cropontology.org) project aims to provide a central place where the crop community can gather to generate such standardized vocabularies and structure them into ontologies. Having standardized ontologies opens the world of the Semantic Web to data integration between different data providers. Crop Ontology is a community-based project, providing a central place for the creation of crop-related ontologies, but it can also be integrated into third-party tools through its Application Programming Interface, providing retrieval of specific terms or a more generic search functionality for all terms. The ontologies are available in RDF format, described using the OWL and RDFS standards, allowing them to be consumed by popular semantic reasoners. We believe that Crop Ontology will lead to better description of crop-related data, improving collaboration between partners and should serve as an example for other scientific fields.